Knowledge about genetics and trust in genetic testing in a mid-size city in Argentina - Mendoza, Marcela (2022)
Public attitudes about genetics appear to depend on the local context. We analyzed survey responses obtained in 2015 from 293 residents of Luján, a city in the province of Buenos Aires, Argentina, who self-assessed their knowledge about genetics and their trust in genetic tests. The survey integrated a larger research project for which consenting adult participants shared demographic and genealogical information and provided saliva samples for genetic ancestry analyses. Participants reported little knowledge but high trust in genetic testing when questioned about knowledge and trust. Well-known media stories of DNA-based forensic genetic investigations to identify the victims of state repression during the military dictatorship may have contributed to the high self-assessment of their genetic knowledge expressed by some participants, regardless of educational attainment. Our analysis provides information that could be used as a baseline to begin unraveling the current level of public trust in genetics in a region of the Global South where genetic testing has become widespread, but people?s knowledge of and trust in genetics remain poorly studied.